Association of systemic inflammatory biomarkers with depression risk: Results from National Health and Nutrition Examination Survey 2005–2018 analyses - Li, Xintong; Huan, Jiaming; Lin, Lin; Hu, Yuanlong (Frontiers in Psychiatry, 2023)
Background/Aim: Depression has become a multiple disease worldwide, and is closely related to the systemic inflammatory response. Methods: Based on the data of the National Health and Nutrition Examination Survey (NHANES), this study included 2514 depressive and 26487 non-depressive adults. The systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI) were used to quantify systemic inflammation. The multivariate logistic regression and inverse probability weighting methods were used to analyze the effect size of SII and SIRI on the risk of depression. Results: After adjusting for all confounders, the above associations of SII and SIRI with depression risk remained significant (SII, OR = 1.02, 95% CI = 1.01 to 1.02, P = 0.001; SIRI, OR = 1.06, 95% CI = 1.01 to 1.10, P = 0.016). Each 100-unit increase in SII was associated with a 2% increase in the risk of depression, while each one-unit increase in SIRI was associated with a 6% increase in the risk of depression. Conclusion: Systemic inﬂammatory biomarkers (SII and SIRI) significantly affected the risk of depression. SII or SIRI can serve as a biomarker of anti-inflammation treatment for depression.